The transition from the 21st to the 22nd dynasty in Thebes as manifested in changes in the wooden funerary stelae of the 22nd dynasty - Swart, L. (Journal for semitics, 2007)
From the late 21st through the 22nd Dynasty there was a visible decrease in the quantity and deterioration of quality of the funerary ensemble of private citizens in Thebes, Egypt. These changes correspond to the new rule by the Libyan-Bubastite kings of the 22nd Dynasty, and the imposition of tighter controls on the funerary ensemble for Theban citizens. This coincides with extensive transformations within the cult of the dead, such as, the abandonment of over-ground tomb structures, the placement of stelae, changes in format and function of the stelae. The second section of this paper, deals with the grouping of stelae into workshops based on predetermined characteristics. The workshops from the early 22nd Dynasty exhibit a standardization of format and style. The iconography is restricted to the employment of a few symbols. The stelae from the late 22nd Dynasty display deterioration in the quality of execution. However, there is a noticeable enrichment of the iconographic repertoire, and a shift back towards the emphasis on Osiris. This is in keeping with political changes of time, namely, the acceptance of the 23rd Dynasty by the denizens of Thebes.,